2005
DOI: 10.1007/s00535-005-1636-6
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of serum ALT normalization after phlebotomy in patients with chronic hepatitis C infection

Abstract: Although the sample number was relatively small, the results of our study suggest that phlebotomy is effective therapy for HCV patients who are nonobese, show little or no steatosis on liver histology, and have a baseline serum ALT level of less than 100 IU/l.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 24 publications
1
19
1
Order By: Relevance
“…Therefore, the present study is in accordance with the literature as it also shows a positive correlation between iron status and liver function markers. Moreover, there are reports which show that in patients with CHC iron depletion by phlebotomy was associated with clinical improvement assessed by significant reduction in liver function markers and iron status prior to [28] and after [29] treatment with interferon a.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, the present study is in accordance with the literature as it also shows a positive correlation between iron status and liver function markers. Moreover, there are reports which show that in patients with CHC iron depletion by phlebotomy was associated with clinical improvement assessed by significant reduction in liver function markers and iron status prior to [28] and after [29] treatment with interferon a.…”
Section: Discussionmentioning
confidence: 96%
“…Hepatic iron concentration has been inversely associated with the response to antiviral therapy [11,12]. Iron removal by phlebotomy improves liver function tests [13,14] and histology [15], increases the probability of sustained HCV eradication with antiviral therapy [1618], and decreases HCC development in CHC patients [19]. Moreover, HCV transgenic mice that are overloaded with iron are prone to develop HCC [20].…”
Section: Introductionmentioning
confidence: 99%
“…The role of iron overload and the response to antiviral therapy in patients with chronic HCV infection has been debated. A few studies suggest that the removal of iron by phlebotomy may have a beneficial effect on markers of cytolysis, oxidative stress, and fibrogenesis [28][29][30]. Several studies have shown an association between iron overload and lower response rates to interferon-alpha monotherapy, which contribute to chronic HCV disease progression [9].…”
Section: Viral Hepatitismentioning
confidence: 99%